Synesthesia and music perception - Bragança,Guilherme Francisco F. (2015)
The present review examined the cross-modal association of sensations and their relationship to musical perception. Initially, the study focuses on synesthesia, its definition, incidence, forms, and genetic and developmental factors. The theories of the neural basis of synesthesia were also addressed by comparing theories emphasizing the anatomical aspect against others reinforcing the importance of physiological processes. Secondly, cross-modal sensory associations, their role in perception, and relationship to synesthesia were analyzed. We propose the existence of a lower, unconscious degree of synesthesia in non-synesthetes. This latent synesthesia (without explicit sensory manifestations) would be functional, aiding the construction of abstract associations between different perceptual fields. Musical meaning might be constructed largely by synesthetic processes, where the sensory associations from sound activate memories, images, and emotions.